IMPLEMENTASI KEBIJAKAN WALI NAGARI DALAM PEMBAYARAN PAJAK BUMI DAN BANGUNAN (PBB) DI NAGARI LIMAU LUNGGO KECAMATAN LEMBANG JAYA KABUPATEN SOLOK - Arya Kusuma, Doddie; Fitri, Raudatul (Universitas Ekasakti, 2022)
Taxes are mandatory contributions to the state owed by individuals or entities, which are used for state purposes. According to law number 28 of 2009 Land and building taxes have been managed by the local government, in Nagari Limau Lunggo there are still many taxpayers who are absent from paying the PBB. The lack of taxpayer initiative has made the regional government of Nagari Limau Lunggo strive to ensure that the community pays their land and building tax on time. Data analysis techniques using data reduction then present the data to conclusions. The results of the analysis in this study resulted in the following conclusions: (1) Implementation of the wali nagari limau lunggo policy in paying land and building taxes so far has been quite good, in its implementation the head of the jorong has an important role in carrying out the policy. (2) In the process of implementing policies in Nagari Limau Lunggo, of course it does not always run smoothly, there are obstacles that are often found in the field by the head of the jorong as an officer who requests payment of land and building taxes in Nagari Limau Lunggo. (3) The mayor of the Limau Lunggo nagari has made various efforts in paying land and building taxes, starting from socialization by the nagari so that people are aware of the importance of paying land and building taxes, then by having a ball pick-up that makes it easier for them to pay PBB.